Malnutrition alters the rates of apoptosis in splenocytes and thymocyte subpopulations of rats - Ortiz, R (Blackwell Science Inc, 2009)
Malnutrition continues to be a major public health problem throughout the developing world. Nutritional deficiencies may be the most common cause of secondary immunodeficiency states in humans. It has been suggested that nutritional imbalances can induce apoptosis in a variety of cell types. The purpose of this study was to examine the effect of severe malnutrition on cell subsets and the frequency of spontaneous and/or dexamethasone-induced cell death in vivo in the thymus and spleen from severely malnourished, lactating rats. Apoptosis frequency was estimated by flow cytometry using annexin-V and terminal transferase-mediated dUTP nick-end labelling assay assays. The results obtained in the present study indicate that malnutrition is associated with a significant increase of spontaneously apoptotic cells in the thymus (9·8-fold) and spleen (2·4-fold). Increase in apoptosis was associated largely with CD4(+)CD8(+) double-positive thymocytes. Unexpectedly, similar frequencies of spontaneous apoptosis of these cells were found in both well-nourished and malnourished rats. In contrast, consistent increases in the apoptosis of CD4(−)CD8(−) double-negative thymocytes were observed in malnourished rats. In addition, single-positive CD8(+) and single-positive CD4(+) thymocytes had higher frequencies of apoptosis in malnourished rats. The frequency of total dexamethasone-induced apoptosis was found to be similar in both groups of animals. Nevertheless, in malnourished dexamethasone-treated animals, the percentage of apoptotic double-negative thymocytes was significantly higher than in well-nourished animals, while the rate of apoptosis was lower among double-positive cells. In general, the thymus appears more sensitive to the effects of malnutrition and dexamethasone than the spleen. Furthermore, double-negative thymocytes appear to be the most affected.